DINAMIKA DIDIKAN GURU KEPADA SISWA BERUJUNG PELAPORAN: ANTARA KEKERASAN ATAU POLA DIDIKAN - Kalis Rubeda, Syukril Agaba; Al Aidrus, Firza Mohammad (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2025)
Teachers and students are two components that are important pillars in the educational process. Teachers act as facilitators of learning and guides for students in achieving academic goals. They create an environment that supports students' intellectual growth and personal development. However, sometimes contradictory situations arise between teachers and students. This can happen due to differences in opinion or interpretation, concerns about assessment or assignments, or even differences in learning and communication styles. This research was conducted using the Literature Research method, with the aim of identifying the factors that influence the dynamics of the teaching and learning process, indicators of violence in the educational process, several cases, and the solutions implemented. The data sources used were research journals, physical books, and articles from highly credible sources. From this study, it was found that teachers must be professional and have boundaries in disciplining students, while students also need to be willing to listen to advice and direction from teachers and try to resolve issues with an open and cooperative approach. It is important for both parties to continue to respect each other and maintain effective communication. Teachers must have patience and empathy in understanding students' perspectives, as well as provide time and space for students to express their opinions. In maintaining good cooperation, it is important for teachers and students to build mutual trust, clear communication, mutual understanding, and respect for each other's differences. In this way, tensions or differences of opinion can be resolved constructively, so that harmonious cooperation can continue.